2019
DOI: 10.1186/s12865-018-0284-6
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin concentrations in people living with HIV/AIDS infected by HHV-8

Abstract: BackgroundMannose-binding lectin (MBL) plays an important role in the innate immune response by activating the complement system via the lectin pathway, and it has been studied in several viral infections; however, the influence of MBL in PLWHA infected with HHV-8 is unknown. The objective of this study was to verify the association of MBL deficient plasma concentrations in HIV/HHV-8 coinfected and HIV monoinfected patients and to correlate these concentrations with HIV viral load and CD4 counts in both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…To determine a biologically plausible fluctuation strength , we analyzed the variability of clone sizes over time in a longitudinal repertoire sequencing study ( Chu et al, 2019 ). We first analyzed how much recently expanded clones contribute to the tail of the clone sizes, and found that only a small fraction of the largest clones in any sample were not already large at the earliest time point ( Figure 4A and Figure 4—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine a biologically plausible fluctuation strength , we analyzed the variability of clone sizes over time in a longitudinal repertoire sequencing study ( Chu et al, 2019 ). We first analyzed how much recently expanded clones contribute to the tail of the clone sizes, and found that only a small fraction of the largest clones in any sample were not already large at the earliest time point ( Figure 4A and Figure 4—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…( C ) Fraction of clones with zero insertions as a function of age and clone size in a simulated cohort using a magnitude of clonal growth rate fluctuations inferred from the longitudinal data. Data source: Chu et al, 2019 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Der p 1 is a cysteine protease allergen and is known to disrupt intracellular tight junction and promote the release of cytokines and alarmins such as TSLP, IL-33 and IL-25 by the protease activity during initial sensitization [ 62 , 63 ]. Der p 2 is known to mimic MD-2, which facilitates signaling through TLR4, leading to airway inflammation [ 64 ]. The current study expands previous findings and demonstrated a novel effect of Dermatophagoides pteronyssinus on airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%